2011
DOI: 10.1002/ffj.2038
|View full text |Cite
|
Sign up to set email alerts
|

Volatile and sensory characterization of Xarel.lo white wines

Abstract: A comprehensive study based on the profiling and quantification of the volatile composition and the application of descriptive sensory analysis of 25 commercial monovarietal white wines (var. Xarel.lo) from different vintages and from representative wine cellars along the Penedés region (Catalonia, Spain) was performed in order to characterize representative wines that are being commercialized under the O.D. Penedés. In addition, relationships between the instrumental (volatile) and sensory variables were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The content of furfural had an increase in the wines in contact with Ch-Ge film during 8 months when compared with wines in contact with the films during 2 months: from 1.7 × 10 6 to 8.9 × 10 6 , p < 0.05 for white wines (Table S1 and Figure 4) and from below the limit of detection (6.0 × 10 3 ) to 4.8 × 10 6 , p < 0.05 for red wines (Table S1 and Figure 5). The occurrence of furfural in wines is usually valorised due to its association with toasted sweet foods [41], giving particular notes to aged white wines in toasted wood barrels [42,43]. Phenylacetaldehyde, benzaldehyde, and 3-methylbutanal, Strecker degradation derived products, known to confer positive distinctive notes to wine aroma, should provide fruity [44], almond [45], and malty [46] aroma scents to wines in contact with Ch-Ge films.…”
Section: Impact Of Chitosan-genipin Films On Wine Volatile Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of furfural had an increase in the wines in contact with Ch-Ge film during 8 months when compared with wines in contact with the films during 2 months: from 1.7 × 10 6 to 8.9 × 10 6 , p < 0.05 for white wines (Table S1 and Figure 4) and from below the limit of detection (6.0 × 10 3 ) to 4.8 × 10 6 , p < 0.05 for red wines (Table S1 and Figure 5). The occurrence of furfural in wines is usually valorised due to its association with toasted sweet foods [41], giving particular notes to aged white wines in toasted wood barrels [42,43]. Phenylacetaldehyde, benzaldehyde, and 3-methylbutanal, Strecker degradation derived products, known to confer positive distinctive notes to wine aroma, should provide fruity [44], almond [45], and malty [46] aroma scents to wines in contact with Ch-Ge films.…”
Section: Impact Of Chitosan-genipin Films On Wine Volatile Compositionmentioning
confidence: 99%
“…, p < 0.05 for red wines (Table S1 and Figure 5). The occurrence of furfural in wines is usually valorised due to its association with toasted sweet foods [41], giving particular notes to aged white wines in toasted wood barrels [42,43]. Phenylacetaldehyde, benzaldehyde, and 3-methylbutanal, Strecker degradation derived products, known to confer positive distinctive notes to wine aroma, should provide fruity [44], almond [45], and malty [46] aroma scents to wines in contact with Ch-Ge films.…”
Section: Impact Of Chitosan-genipin Films On Wine Volatile Compositionmentioning
confidence: 99%
“…Our results reveal that tasters differentiated the wines according to sensory attributes as it has been appointed in other studies (Lund et al 2009;Muñoz-González et al 2011). However, according to PCA result, olfactory, taste and visual characters showed different weight for red, white and red wines.…”
Section: Sensory Descriptions Analysis Of the Tasted Winessupporting
confidence: 78%
“…Cabernet-Sauvignon (Tao et al 2009) or Pinot noir (Girard et al 2001); studies related to this topic are available in Spanish commercial wines (de la Presa-Owens and Noble 1995;Vilanova et al 2008;Rodríguez-Nogales et al 2009;Muñoz-González et al 2011). However, descriptive analysis of the not commercial wines done with local or autochthonous grape varieties are not been very usual (Gutierrez Afonso et al 1998) despite of the great interest that this varieties are arousing nowadays, since oenology production is a dynamic process of that need to be always adapted to changes and demands on wine market (Bertuccioli 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Among the esters, three medium-chain fatty acid ethyl esters, ethyl hexanoate, ethyl octanoate, and ethyl decanoate, were particularly prominent. These compounds are known for their fruity notes in young white wines [35]. Previous studies have identified ethyl hexanoate in corks [13], and research has shown that other ethyl esters and acetates, such as ethyl butyrate or butyl acetate, can migrate from cork to wine solutions, potentially enhancing wine aroma [11].…”
Section: Resultsmentioning
confidence: 99%